Factors influencing the choice of internal medicine as a career among undergraduate medical students - I. Elzain, Yamin; Alawad, Awad Ali Mohamed Ahmed; S. Khan, Waleed; O. Khalil, Hassan; M. Abdelrazig, Yousif; B. Ahmed, Omer; A. Adam, Omeralfaroug (International Journal of Health, 2014)
Background: Medical students are the future doctors in any country. The lack or surplus of medical school interest in specialties influences and affects the health services in a country. Objective: In our study we evaluated the interest of medical students in Internal Medicine at a University in Sudan. Methods: A cross-sectional study was conducted in September 2013 at Faculty of Medicine, University of Medical Sciences and Technology (UMST), Khartoum, Sudan. A self-administered questionnaire was given to 887 male and female students enrolled at UMST. Results: A total of 887 questionnaires were handed out, of these 647 questionnaires were returned (response rate of 73%). Of the returned questionnaires 604 were valid and considered. Table 1 shows the general characteristics of the valid responses. The majority of our respondents were females 371 (61.4%) and 233 students were males (38.6%). There were 142 students interested in internal medicine. Of them, 95(21.3%) were in pre-clinical years, 47(29.6%) clinical, 25.3% were male and 22.4% were female. Amongst the subspecialties within medicine, 33.1% of students chose Cardiology as their first choice subspecialty, followed by Internal Medicine (26.8%), Neurology (13.4%) and Dermatology (11.3%). Conclusion: Medicine is second most popular specialty selected by medical students. The highest selected sub-specialty was cardiology. The main reasons for selecting Medicine as a career is personal interest, followed by being helpful to the community, and lastly job opportunities. Keywords: Career Choice, Internal Medicine, Medical Students.